THE IMPACT OF COMPUTERIZED EXAM FEATURES, EFFECTIVE EXAM IMPLEMENTATION, TOWARD STUDENT SATISFACTION - Hendro, Indra; Wiley, Victor; Lucas, Thomas (IJIET (International Journal of Indonesian Education and Teaching), 2022)
This paper intends to examine in detail the relationship between computerized exam features and effective exam implementation toward student satisfaction. The main goal is to examine the synergistic relationships which impacting student satisfaction after they using a computerized standardization exam in the college setting. Design/methodology/approach –an initial exploratory analysis was conducted methodically to confirm the proposed model through a structural equation modeling approach. The computerized exam features (especially, clear wording instruction and exam rulebook) had high effects on student satisfaction. Secondly, Effective Exam implementation (especially, efficient effort, time and cost) also impacted student satisfaction. Thirdly, the statistical testing result confirmed a joint impact of computerized exam features and effective exam implementation toward student satisfaction. The conceptual model has been validated to understand the role of both variables toward student satisfaction. However, there is lack of empirical validation and generalization of the model into wider scope due to limited time of research and a small number of the participant which suggest future research.